Epidemiology of chronic kidney diseases in the Republic of Guinea; future dialysis needs - Alpha Oumar Bah; Cisse Lamine; Mamadou Cellou Balde; Mamadou Lamine Yaya Bah; Lionel Rostaing (Society of Diabetic Nephropathy Prevention, 2015)
Background: Chronic kidney disease (CKD) is increasing worldwide and can lead to end-stage renal disease (ESRD). Objectives: Because few patients with ESRD in the Republic of Guinea have access to haemodialysis, we retrospectively evaluated the prevalence of CKD, ESRD and access to supportive therapies. Patients and Methods: 579 CKD patients (304 males; mean age: 44 ± 16 years) were admitted into Conakry nephrology department, the only centre in the Republic of Guinea, between 2009 and 2013. Most patients (63%) resided within Conakry (the capital), 12.5% came from lower Guinea, 11.7% from middle Guinea, 7.9% from upper Guinea and 4.8% from forest Guinea. Results: Reasons for referral were increased serum creatinine (49.5%), hypertension (27%) and diffuse edema (17%). Also, 11% were diabetic, 12.5% were smokers, 17% were HIV-positive, 8.3% were HBV-positive and 15% were HCV-positive. The most frequent symptom at admission was nausea/vomiting (56%). Upon admission, 70.5% of patients already had ESRD. Although no kidney biopsies were performed it was assumed that 34% and 27% of patients had vascular nephropathy and chronic glomerulonephritis, respectively. Of the 385 ESRD patients, only 140 (36.3%) had access to haemodialysis (two sessions/week, 4 hours each). Most patients that received haemodialysis resided within the Conakry region (P < 0.0001). There were significant associations between mortality and (i) terminal stage of CKD (P = 0.0005), (ii) vascular nephropathy (P = 0.002), and (iii) nephropathies of unknown origin (P = 0.0001). Conclusions: A fourfold increase in haemodialysis machines is needed in Conakry, plus four new nephrology/haemodialysis centres within the Republic of Guinea, each holding ≥30 haemodialysis machines.